2016
DOI: 10.15171/ijhpm.2016.74
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Public Policies to Address Non-communicable Diseases in the Caribbean Country of Barbados: The Importance of Problem Framing and Policy Entrepreneurs

Abstract: Background: Government policy measures have a key role to play in the prevention and control of non-communicable diseases (NCDs). The Caribbean, a middle-income region, has the highest per capita burden of NCDs in the Americas. Our aim was to examine policy development and implementation between the years 2000 and 2013 on NCD prevention and control in Barbados, and to investigate factors promoting, and hindering, success. Methods: A qualitative case study design was used involving a structured policy document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
4
28
0
Order By: Relevance
“…Urban populations in Africa tend to be very diverse by education, religion, socioeconomic status and culture [5]. As a result, NCD prevention and control policies and programs need to be tailored to cater for variations at population levels [107]. In a review CVD policies in Kenya found no standalone policies for CVD management and care but some aspects of CVD policy were covered in general NCD policy document [108].…”
Section: Weak Policiesmentioning
confidence: 99%
“…Urban populations in Africa tend to be very diverse by education, religion, socioeconomic status and culture [5]. As a result, NCD prevention and control policies and programs need to be tailored to cater for variations at population levels [107]. In a review CVD policies in Kenya found no standalone policies for CVD management and care but some aspects of CVD policy were covered in general NCD policy document [108].…”
Section: Weak Policiesmentioning
confidence: 99%
“…Most of the articles in our sample (82.6%) use a single case study analysis. Thus, comparative analysis is less common (for a comparative article, see Unwin, Samuels, Hassell, Brownson, & Guell, 2016), although they may add to our understanding of the phenomenon of policy entrepreneurship.…”
Section: Countriesmentioning
confidence: 99%
“…NCDs and the SIDS environment are both complex, dynamic systems that together, present an even more multifaceted set of issues. 15,16 The Cynefin model of decision-making ( Fig. 1) highlights that is not enough to consider 'best practice' strategies in complex adaptive systems, as such strategies specify a simple cause and effect pathway, encouraging a reductionist view of complex issues, such as NCDs.…”
Section: The Complexity Of Dohad In Sidsmentioning
confidence: 99%